The Influence Of Service Quality, Facilities, And Location On Customer Satisfaction At Pushup Coffee Semarang - Clarisa Cristabel Rich Yunianto; Mukhamad Kholil Aswan (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This study aims to determine the effect of service quality, facilities, and location on customer satisfaction at Pushup Coffee Semarang. This research is research using quantitative methods carried out in Semarang City. The research population is consumers of Pushup Coffee Semarang, where the population is 15,445 people. Samples were taken using accidental sampling technique, and data was collected using a questionnaire. The results of the research show that: (1) Service quality variables have a positive effect on consumer satisfaction by obtaining a constantan coefficient value of 0.371. (2) The facility variable has a positive effect on consumer satisfaction by obtaining a Constantan coefficient value of 1.096. (3) The location variable has a negative effect on consumer satisfaction by obtaining a constantan coefficient value of – 690.